Phytochemicals in the Prevention and Treatment of SARS-CoV-2-Clinical Evidence - Katarina Bijelić; Maja Hitl; Nebojša Kladar (MDPI AG, 2022)
The first case of SARS-CoV-2 infection was reported in December 2019. Due to the rapid spread of the disease and the lack of adequate therapy, the use of plants that have a long history in the treatment of viral infections has often been considered. The aim of this paper is to provide a brief review of the literature on the use of phytochemicals during the new pandemic. An extensive search of published works was performed through platforms Google Scholar, PubMed, Science Direct, Web of Science and Clinicaltrials.gov. Numerous preclinical studies on the use of phytochemicals (quercetin, curcumin, baicalin, kaempferol, resveratrol, glycyrrhizin, lycorine, colchicine) against SARS-CoV-2 have shown that these components can be effective in the prevention and treatment of this infection. Clinical research has proven that the use of black cumin and green propolis as well as quercetin has positive effects. As for other phytochemicals, in addition to preclinical testing which has already been carried out, it would be necessary to conduct clinical tests in order to assert their effectiveness. For those phytochemicals whose clinical efficacy has been proven, it would be necessary to conduct research on a larger number of patients, so that the conclusions are more representative.